Effect of Forming Holes and Moistening Water Temperature on Some physical Quality Characteristics of Poultry Feed Pellets - Aabbas, Basim Aboud (Al-Mukhtar Journal of Sciences, 2022)
The research aims to investigate the effect of feed manufacturing conditions on some significant physical traits of feed pellets for poultry feeding. The study was conducted using a factorial experiment of two factors that included the effect of the studied forming holes’ diameters at 2.5 and 4.5 mm, and the feed pellet moistening water temperature at 25 and 40 C°. Hence to find out their effect on the broken pellets, unbroken pellets, pellet expansion, and dust ratio. The results showed that increasing the diameter of the forming holes from 2.5 to 4.5 mm significantly affected the decrease in unbroken pellets, the increase in the percentage of broken pellets, pellet expansion ratio, and dust ratio. Increasing the temperature of the water from 25 to 40 C°, led the percentage of unbroken pellets to increase significantly and the percentage of broken pellets, and pellet expansion ratio decreased significantly. Whereas no significant effect on dust was recorded. The highest resistance to pellet breakage was 96.66%, the least percentage of unbroken pellets was of 3.38%, and the lowest dust content was 0.48%, with 2.5 mm holes and 40 C°. The lowest expansion ratio was 6.13% with 2.5 mm holes and 25 C°. It was concluded that the increase in the diameter of the forming holes led to an increase in the percentage of broken pellets, the percentage of expansion ratio, and the percentage of dust. Increasing temperature of the water led to an increase in the percentage of unbroken pellets, while there was no significant effect on the percentage of dust. We recommend increasing the diameter of the forming holes according to the age of the animals and using steam for moistening rather than hot water.